2017
DOI: 10.1590/s0100-204x2017001100001
|View full text |Cite
|
Sign up to set email alerts
|

Biological parameters and thermal requirements of Trichogramma pretiosum reared on Helicoverpa armigera eggs

Abstract: -The objective of this work was to determine the biological parameters and thermal requirements of Trichogramma pretiosum TM strain reared on Helicoverpa armigera eggs. A card containing 20 eggs of H. armigera was offered for each T. pretiosum female, at temperatures of 18, 20, 22, 25, 28, 30 and 32°C. All life stages of T. pretiosum were observed under the given temperature conditions. The optimum temperature for the parasitism of T. pretiosum was 25°C, and the highest longevity was found at the same temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(19 reference statements)
2
2
0
2
Order By: Relevance
“…Our result revealed that the optimum temperature for emergence (survival) of T. euproctidis was 32.5°C (90%), and these values are similar to other Trichogramma species as reported by Scholler and Hassan 2001 , Haile et al 2002 , El-Wakeil 2007 ( T. evanescens ), Bari et al 2015 ( Trichogramma zahiri Polaszek (Hymenoptera: Trichogrammatidae)) and Carvelho et al 2017 ( Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae)). Lessard and Boivin (2013) claimed that suboptimal temperature causes decreased energy, metabolic dysfunction, and mortality in immature stages and consequently had negative effect on the emergence rates of Trichogramma wasps.…”
Section: Discussionsupporting
confidence: 87%
“…Our result revealed that the optimum temperature for emergence (survival) of T. euproctidis was 32.5°C (90%), and these values are similar to other Trichogramma species as reported by Scholler and Hassan 2001 , Haile et al 2002 , El-Wakeil 2007 ( T. evanescens ), Bari et al 2015 ( Trichogramma zahiri Polaszek (Hymenoptera: Trichogrammatidae)) and Carvelho et al 2017 ( Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae)). Lessard and Boivin (2013) claimed that suboptimal temperature causes decreased energy, metabolic dysfunction, and mortality in immature stages and consequently had negative effect on the emergence rates of Trichogramma wasps.…”
Section: Discussionsupporting
confidence: 87%
“…Also in the study by Oliveira et al (2017) there was also a reduction in the values of parasitism, emergence, adult egg period and sexual ratio, when the temperature ranged from 25 °C to 33 °C. Similar tendency were also observed in other studies, regardless of the host (Carvalho et al, 2017;Milanez, Carvalho, Lima, & Pratissoli, 2018). However, despite the temperature stress condition of T. pretiosum females in this study, it was observed that the longevity, tibial length, number of parasitized eggs and adult emergence rate increased.…”
Section: Resultssupporting
confidence: 91%
“…Among the climatic factors, the temperature is the one that exerts more influence on the parasitoids, being one of the main regulators of insects metabolism (Angilletta, Niewiarowski, & Navas, 2002). In laboratory conditions, the constant temperature of 25 °C was shown to be the most favorable for the maintenance of T. pretiosum activities, but when subjected to extremes between 28 °C and 33 °C there was a significant reduction in longevity, parasitism, emergence, developmental cycle and sexual ratio (Bueno, Parra, & Freitas Bueno, 2012;Carvalho et al, 2017;Oliveira, de Oliveira, Breda, França, & Duarte, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sifat parasitoid akan cenderung mengurangi aktifitas dalam memarasit inangnya pada suhu yang rendah serta akan meningkat seiring dengan meningkatnya suhu. Laju parasitasi terhadap kepadatan inang akan relatif sama, jika suhu yang ditemukan adalah sekitar 25 0 -30 0 C (Carvalho et al, 2017). Suhu yang terlalu cepat mengalami perubahan atau terlalu tinggi akan menurunkan aktifitas parasitoid, karena parasitoid akan lebih cepat kehilangan banyak cairan jika terus aktif bergerak Carvalho, et al, 2017).…”
Section: Hasil Dan Pembahasanunclassified